PUISI MAGIS (PANGISSENGENG): BENTUK DAN MAKNA (Magic Poetry Pangissengeng: Form and Meaning) - Syamsurijal Rasyid; Musayyedah Husain (Balai Bahasa Sulawesi Selatan, 2014)
Local tradition especially poetry needs to analyze since it becomes the part of local culture that is inherited from generation to generation based on its need. The existence of literary work not only change in the form since it is transferred by oral but also in its frequency usage over the time along cultural tradition movement happens, finally it is scattered and forgotten. Magic poetry (spell) is oral tradition which is still found in the society even though its existence is only known by certain people. The writing is intended to find out the kind, meaning, and form of spell (pangissengeng). Method used is descriptive qualitative with inventory and listening technique. Result of the research is the spell implying mystic power that could influence others or the speller himself. The spell functions as philtre (cenningrara), silencer (paggerak), affirmative (parimbolog), and healer (pajjappi).